OPTIMALISASI PRODUK TURUNAN KELAPA MENJADI NATA DE COCO DAN PEMBUDIDAYAAN TOGA DI DESA SANA DAJA - Muhammad Ramdani Zain; Tajus Subqi (Jurnal Riset Multidisiplin Edukasi, 2025)
Sana Daja Village, Pasean District, Pamekasan Regency, is known for its abundant coconut potential, but its use is still limited to the sale of raw coconuts with low economic value. In addition, many family medicinal plants (TOGA) grow naturally, but have not been optimally managed. The Community Service Program (PkM) aims to optimize coconut derivative products into nata de coco and cultivate TOGA to be processed into instant herbal medicine. This activity was carried out from August 26 – September 24, 2025 with three main stages: preparation, implementation, and evaluation. The results of the activity showed: (1) The training on making nata de coco was attended by 35 PKK women, with 85% of participants able to produce high-quality nata de coco and understand its market potential; (2) TOGA cultivation training and instant herbal medicine processing involved 30 residents, where 90% of participants succeeded in making instant herbal medicine from ginger, turmeric, and temulawak with simple packaging; (3) Post-test showed that 88% of participants understood the economic benefits of coconut derivative products and TOGA, although 12% still needed further assistance for marketing. This program is expected to improve the economic welfare of the community through the use of local resources.